Digital competence of faculty members in health sciences measured via self-reflection: current status and contextual aspects - Halil Ersoy; Cigdem Baskici; Aydan Aytar; Raimonds Strods; Nora Jansone Ratinika; António Manuel Lopes Fernandes; Hugo Neves; Aurelija Blaževičienė; Alina Vaškelytė; Camilla Wikström-Grotell; Heikki Paakkonen; Anne Söderlund; et al. (PeerJ)
This descriptive study aims to determine the digital competence level of faculty members who teach in the health sciences, empirically considering possible contextual aspects. Two data collection instruments were used: a self-reflection questionnaire to assess digital competence, and a survey querying demographics and aspects of teaching and learning context. In total, 306 health sciences faculty members from six universities voluntarily participated the study. The results revealed that a majority of the faculty members have intermediate (integrator or expert) level of digital competence, which is described as being aware of the potential use of digital technology in teaching and having a personal repertoire for its use under various circumstances. Age, digital teaching experience, perception of work environment, and previous teaching experience in fully- or partially-online courses were identified as influencing factors for digital competence. Faculty members in health sciences were able to integrate digital technologies in their teaching practices. Health education institutions may facilitate the use of digital technologies in teaching and learning environments. Moreover, institutions or stakeholders should consider that digital competence requires practice and experience in meaningfully-designed digital environments and tools.